Do Emergency Ultrasound Fellowship Programs Impact Emergency Medicine Residents' Ultrasound Education?. (1st June 2014) - Adhikari, Srikar; Raio, Christopher; Morrison, Daniel; Tsung, James; Leech, Stephen; Meer, Jehangir; Lyon, Matthew; Lopez, Fernando; Akhtar, Saadia
Abstract : Objectives: Recent years have seen a rapid proliferation of emergency ultrasound (EUS) programs in the United States. To date, there is no evidence supporting that EUS fellowships enhance residents' ultrasound (US) educational experiences. The purpose of this study was to determine the impact of EUS fellowships on emergency medicine (EM) residents' US education. Methods: We conducted a cross‐sectional study at 9 academic medical centers. A questionnaire on US education and bedside US use was pilot tested and given to EM residents. The primary outcomes included the number of US examinations performed, scope of bedside US applications, barriers to residents' US education, and US use in the emergency department. The secondary outcomes were factors that would impact residents' US education. The outcomes were compared between residency programs with and without EUS fellowships. Results: A total of 244 EM residents participated in this study. Thirty percent (95% confidence interval, 24%–35%) reported they had performed more than 150 scans. Residents in programs with EUS fellowships reported performing more scans than those in programs without fellowships ( P = .04). Significant differences were noted in most applications of bedside US between residency programs with and without fellowships ( P < .05). There were also significant differences in the barriers to US education between residency programs with and without fellowships ( P < .05). Conclusions: Emergency US fellowship programs had a positive impact on residents' US educational experiences. Emergency medicine residents performed more scans overall and also used bedside US for more advanced applications in programs with EUS fellowships.